Effects of Poly-herbal Tablet as Herbal Medicine on Lipid Level - Woro Rukmi Pratiwi; Eti Nurwening Sholikhah; Dwi Aris Agung Nugrahaningsih; Mia Munawaroh Yuniyanti; Mustofa Mustofa; Ngatidjan Ngatidjan (Majalah Obat Tradisional, 2019)
Dyslipidemia is one of the high-risk factors that cause cardiovascular disease and the prevalence is increasing all the time. Garlic (Alii sativi) has been suggested to reduce serum lipid level. Poly-herbal is herbal medicine that has been widely used in Indonesia, and it contains Alii sativi, Belericae fructus, Curcumae aeroginosae, and Amomi fructus extract. This study aimed to evaluate the effects of poly-herbal tablet on lipid levels in dylipidemia subjects. The study was conducted for 6 weeks on 58 dyslipidemic subjects. The subject was divided into 2 groups. Group 1 was given Poly-herbal with the dose 2x1200 mg, and group 2 was not given anti-dyslipidemic drugs (control group). Serum lipid level (total cholesterol, LDL, HDL, and triglycerides) were checked before the treatment (H0) and after the treatment (M6). There was a significant difference on the reduction of serum lipids level between the group that given Poly-herbal vs control group, respectively total cholesterol (-12.04±3.2 vs 8.38±4.3; p=.000),  LDL (-4.42±2.8 vs 6.93±4.7; p=.049) and HDL (-2.62+1.0 vs 3.31+1.4; p=.005). Triglyceride level on Poly-herbal group is not significantly decreased. In Poly-herbal group there was also a decrease in HDL levels which was not statistically significant (-2.62±1, p=.015). This is probably due to the HDL baseline in the control group included in the normal HDL category (57.38 ± 14.9) so that the HDL levels after being given treatment did not increase. This study suggests that using Poly-herbal in dyslipidemia subjects can reduce the level of total cholesterol and LDL.